Case Report: Key Role of the Impella Device to Achieve Complete Revascularization in a Patient With Complex Multivessel Disease and Severely Depressed Left Ventricular Function - Monizzi, Giovanni; Grancini, Luca; Olivares, Paolo; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2021)
Background: Left ventricle (LV) assist devices may be required to stabilize hemodynamic status during complex, high-risk, and indicated procedures (CHIP). We present a case in which elective hemodynamic support with the Impella CP device was essential to achieve complete revascularization with PCI in a patient with complex multivessel disease and severely depressed LV function. Case Summary: A 45-year-old male with no previous history of cardiovascular disease presented to the emergency department for new onset exertional dyspnoea. Echocardiography showed severely depressed LV function (EF 27%) that was confirmed with cardiac magnetic resonance. Two chronic total occlusions (CTOs) of the proximal right coronary artery (RCA) and left circumflex coronary artery (LCx) were found at coronary angiography. After Heart Team evaluation, PCI with Impella hemodynamic support was planned. After crossing and predilating the CTO of the LCx, ventricular fibrillation (VF) occurred. No direct current (DC) shock was performed because the patient was conscious thanks to the support provided by the Impella pump. About 1 min later, spontaneous termination of VF occurred. Afterwards, the two CTOs were successfully treated with good result and no complications. Recovery of LV function was observed at discharge. At 9 months, the patient had no symptoms and echocardiography showed an EF of 60%. Discussion: In this complex high-risk patient, hemodynamic support was essential to allow successful PCI. It is remarkable that the patient remained conscious and hemodynamically stable during VF that spontaneously terminated after 1 min, likely because the Impella pump provided preserved coronary perfusion and LV unloading. This case confirms the pivotal role of Impella in supporting CHIP, particularly in patients with multivessel disease and depressed LV function.